The Ecumenical Vision of John A. Mackay - Moorhead, James H. (Theology today, 2014)
Despite a religious background that he himself later called “completely parochial,” John Mackay matured into a Christian leader with a remarkably inclusive vision. “If it is to be truly ecumenical,” Mackay declared, “the Church must transcend every boundary … As the Church, it must rise above every human division.” To go beyond such boundaries, Mackay not only engaged in standard ecumenical ventures such as the YMCA and the World Council of Churches, he also raised his voice to protest social and political evils, whether found in Nazi Germany, the Communist Bloc, or the United States. Mackay also reached out to movements such as Pentecostalism, often ignored by many mid-twentieth century ecumenical Protestants. Beneath Mackay’s inclusiveness lay his faith in a Christ in whom all things ultimately cohere and who even now leads his people beyond existing boundaries toward the fulfillment of cosmic unity in Him.